Genealogies of religion: discipline and reasons of power in Christianity and Islam - Asad, Talal (A Johns Hopkins paperback, 1993)
"In Genealogies of Religion Asad explores how religion as a historical category emerged in the West and has come to be applied by scholars, journalists, and politicians as a universal concept. The idea that religion has undergone a radical change since the Christian Reformation - from totalitarian and socially repressive to private and relatively benign - is a familiar part of the story of secularization. It is often invoked to explain and justify the liberal politics and world-view of modernity. And it leads to the view that "politicized religions" threaten both reason and liberty. Asad's essays explore and question all these assumptions. He argues that "religion" is a construction of European modernity, a construction that authorizes - for Westerners and non-Westerners alike - particular forms of "history making." Asad examines aspects of this authorizing process in the so-called fundamentalism of Saudi Arabia, in the Rushdie affair in Great Britain, and in other phenomena."--BOOK JACKET